2017
DOI: 10.1016/j.jcin.2017.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Measurements for the Selection of Patients With Renal Artery Stenosis

Abstract: Interventions targeting renal artery stenoses have been shown to lower blood pressure and preserve renal function. In recent studies, the efficacy of catheter-based percutaneous transluminal renal angioplasty with stent placement has been called into question. In the identification of functional coronary lesions, hyperemic measurements have earned a place in daily practice for clinical decision making, allowing discrimination between solitary coronary lesions and diffuse microvascular disease. Next to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…15 Direct assessment of renal hemodynamics using combined intrarenal pressure and flow velocity measurements may provide further insight in renal pathophysiology and serve as a benchmark for future noninvasive diagnostics in patients with CKD. 16,17 Recently, we have shown that measurement of intrarenal hyperemic flow velocity during dopamine-induced hyperemia is feasible and reproducible. 18 The renal circulation consists of afferent and efferent arteriolar systems, which can more or less independently influence GFR.…”
mentioning
confidence: 99%
“…15 Direct assessment of renal hemodynamics using combined intrarenal pressure and flow velocity measurements may provide further insight in renal pathophysiology and serve as a benchmark for future noninvasive diagnostics in patients with CKD. 16,17 Recently, we have shown that measurement of intrarenal hyperemic flow velocity during dopamine-induced hyperemia is feasible and reproducible. 18 The renal circulation consists of afferent and efferent arteriolar systems, which can more or less independently influence GFR.…”
mentioning
confidence: 99%
“…Variants of FFR have been used to assess the severity of renal artery stenosis as summarised in the review by van Brussel et al 51 . Their systematic review included 6 studies examining the efficacy of hyperaemic haemodynamic indices in guiding the therapeutic strategy on renal artery stenosis (the number of patients ranged from 17–62).…”
Section: Challenges and New Application Areasmentioning
confidence: 99%
“…Этиология, патогенез не вызывают затруднений и давно уже выяснены. Известны риски, предрасполагающие факторы для развития атеросклероза в сосудах почек [1][2][3]. Тем не менее до сих пор нет единого систематизированного подхода в тактике ведения данных пациентов.…”
Section: обзор литературы введениеunclassified